2020
DOI: 10.3390/polym12020459
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of Porous Protein-Based Polymers and Their Liquid Absorption Characteristics

Abstract: The production of porous wheat gluten (WG) absorbent materials by means of extrusion processing is presented for the future development of sustainable superabsorbent polymers (SAPs). Different temperatures, formulations, and WG compositions were used to determine a useful protocol that provides the best combination of porosity and water swelling properties. The most optimal formulation was based on 50 wt.% WG in water that was processed at 80 °C as a mixture, which provided a porous core structure with a dense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 50 publications
1
31
1
Order By: Relevance
“…The 70/30 gluten/glycerol weight ratio was selected based on previous work, which showed that this composition yielded a combination of mechanically flexible and ductile films and good extrudability . When using the foaming agents SBC and ABC, 2.5 g (5 wt %) of these were added during the mixing, and the WG content was lowered to 32.5 g, following the previous optimization work with SBC . The mixture was processed with two different types of equipment: I, a conical fully intermeshing and corotating double-screw microcompounder (DSM Xplore 5 cc, The Netherlands); II, a single screw extruder (Brabender Do-Corder C3, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 70/30 gluten/glycerol weight ratio was selected based on previous work, which showed that this composition yielded a combination of mechanically flexible and ductile films and good extrudability . When using the foaming agents SBC and ABC, 2.5 g (5 wt %) of these were added during the mixing, and the WG content was lowered to 32.5 g, following the previous optimization work with SBC . The mixture was processed with two different types of equipment: I, a conical fully intermeshing and corotating double-screw microcompounder (DSM Xplore 5 cc, The Netherlands); II, a single screw extruder (Brabender Do-Corder C3, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The strong cohesive properties and viscoelastic nature of WG , make it a potential material option for producing foams through conventional extrusion. The production of WG foams from aqueous solutions through lyophilization has been reported ,, and also using other techniques like microwave heating. ,, Moreover, WG foams with a range of built-in features have been made, including improved electric and thermal conductance, ,, superabsorbency, , and microbial resistance. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the extrusion processing parameters using the best ratios of wheat starch/glycerol/gluten/sodium bicarbonate (100/46/25/1) resulted in a higher and more stable expansion (9.1) at a screw speed and input rate of 300 rpm and 21 kg/h, respectively. In general, a feed with a water content of 15–18% is regarded best for producing foams with the maximum expansion ratio [ 277 ]. Extrusion for biofoam manufacturing will necessitate further experimental and modeling studies to improve theoretical knowledge and technical processes, as it is a necessary operation in practically all industrial applications.…”
Section: Manufacturing Process For Biofoamsmentioning
confidence: 99%
“…Gluten, like most commodity polymers (e.g. polyethylene and polypropylene), can be processed using established methods of compression moulding, injection moulding, extrusion and thermoforming to create a variety of shapes that include thin films and complex geometries (Capezza et al, 2020b;Rasel et al, 2016;Redl et al, 1999). Furthermore, gluten can also be electrospun into nanofibre membranes.…”
Section: Introductionmentioning
confidence: 99%